2017
DOI: 10.1589/jpts.29.1996
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the pain-relieving effects of transcutaneous electrical nerve stimulation applied at the same dermatome levels as the site of pain in the wrist joint

Abstract: [Purpose] The purpose of this study was to develop a proposal for an effective interventional option for therapeutic stimulation sites by comparing the pain-relieving effect of transcutaneous electrical nerve stimulation (TENS) applied to the same dermatome level of the contralateral sites of the dorsal wrist joint with the pain or the neck, or both sites simultaneously. [Subjects and Methods] A control was first established by triggering pain in the left dorsal wrist joints of adult females by using heat stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In the present study, the 1kHz Aussie current was used in students with chronic non-specific neck pain, and the intensity was assessed by the VAS and the functional disability by the NDI. Both are validated and well-established in the literature 10,13,15 . Despite the reports that the electrical stimulation positively affects the treatment of individuals with neck pain, such as TENS 12,16,17 and the Interferential 11 , in this study, the variables related to pain and disability did not present differences in relation to the baseline values or intergroup.…”
Section: Discussionmentioning
confidence: 82%
“…In the present study, the 1kHz Aussie current was used in students with chronic non-specific neck pain, and the intensity was assessed by the VAS and the functional disability by the NDI. Both are validated and well-established in the literature 10,13,15 . Despite the reports that the electrical stimulation positively affects the treatment of individuals with neck pain, such as TENS 12,16,17 and the Interferential 11 , in this study, the variables related to pain and disability did not present differences in relation to the baseline values or intergroup.…”
Section: Discussionmentioning
confidence: 82%
“…It was not possible to apply kinesiology tapes directly over the QST measurement sites. However, it can be extrapolated from the findings of a study that compared pain-relieving effects of transcutaneous electrical nerve stimulation applied at the same dermatome levels as the site of pain [33] that the application of kinesiology tapes in this study covered the same dermatome levels as the QST measurement areas and would have the potential to trigger modulatory mechanisms of the relevant segment of the nociceptive system.…”
Section: Methodsmentioning
confidence: 99%
“…The contralateral location was at the opposite dorsal wrist joint and the proximal location was at the neck in the same dermatomes as the pain site. 113 The outcome measure was the pain VAS. Both the contralateral and proximal sites produced a statistically significant reduction in pain compared to pretreatment baseline.…”
Section: Experimental Human Painmentioning
confidence: 99%
“…Additional studies using experimental human-pain models have shown that TENS applied to one side of the body evokes an analgesic response in the homologous region on the contralateral side. 28,113,114,[117][118][119][120][121][122] Buonocore et al showed that TENS applied to the cutaneous distribution of the superficial radial nerve increased the heat-pain threshold in the dorsal hand bilaterally. 117 Lehmann and Strian showed that both ipsilateral and contralateral TENS reduced tonic thermal pain relative to placebo.…”
Section: Experimental Human Painmentioning
confidence: 99%